TELAAH KONSEPTUAL IMPLEMENTASI SLOGAN HUBB AL-WATHAN MIN AL-IMAN KH. HASYIM ASY’ARI DALAM PENDIDIKAN KARAKTER CINTA TANAH AIR - Nur Rofiq (Universitas Negeri Medan, 2018)
ABSTRACT This study attempts to answer the above problems by examining the conceptual implementation of the hubb slogan al-wathan min al-iman KH. Hasyim Asy'ari in the education of the character of love for the homeland. Hubb al-wathan's slogan min al-iman echoed by KH. Hasyim Asyari as a lighter of the fighting spirit of the santri to maintain the independence of the nation, instill nationalism and patriotism which evoke the courage to make sacrifices of soul, body and property as well as scientific credibility and character of KH. Hasyim Asy'ari is a combination of his strong religious character, national commitment, leadership, and broad insight into his state. Based on a conceptual review of the implementation of the hubb slogan al-wathan min al-iman KH. Keywords: Al-Wathan Min Hubb Al-Faith, Education, Character